Association between preoperative platelet count and transjugular intrahepatic portosystemic shunt procedure-related hemorrhage in cirrhotic patients: a retrospective study - Li, Ying; Xu, Jisen; Quan, Xin; Wei, Bo; Tai, Yang; Wu, Hao (Frontiers in Medicine, 2025)
ObjectiveTransjugular intrahepatic portosystemic shunt (TIPS) is a high-bleeding-risk vascular intervention. The association between TIPS-related hemorrhage and preprocedural platelet (PLT) count remains unclear.MethodsThis was a retrospective cohort study including patients receiving TIPS procedures for complications related to portal hypertension due to liver cirrhosis between 2011 and 2022. Logistic regression and subgroup analyses were performed to evaluate the relationship between TIPS-related hemorrhage and preprocedural PLT count. Patients were divided into two groups based on a PLT threshold of 50 × 109/L. Furthermore, patients with PLT count < 50 × 109/L were stratified into two subgroups based on a threshold of 20 × 109/L. The primary endpoint was TIPS procedure-related hemorrhage.ResultsA total of 632 patients with liver cirrhosis who underwent TIPS were categorized into two groups based on their PLT counts of 50 × 109/L. The incidence of TIPS-related hemorrhage was 2.8% in the PLT < 50 × 109/L group (n = 417) and 1.9% in the PLT ≥ 50 × 109/L group (n = 215) (95% CI: 0.23–1.97; P = 0.480). In subgroup analysis, the bleeding rate was 0% in PLT < 20 × 109/L group (n = 10) and 2.9% in PLT 20–50 × 109/L group (n = 205). No statistically significant intergroup differences in bleeding rates were found (95% CI: 0–9.7; P = 0.501). In the univariate and multivariate analysis, advanced age is the independent risk factor for TIPS-related bleeding (OR = 1.054, 95% CI: 1.006–1.105, P = 0.028).ConclusionThis study revealed that preoperative PLT count is not associated with TIPS procedure-related hemorrhage in patients with cirrhosis. Patient age should be carefully considered in the preoperative assessment.